Reliabilitas dan Validitas Konstruk Academic Buoyancy di Indonesia - Meilani Rohinsa Sitompul (Humanitas (Jurnal Psikologi), 2021)
Research on the reliability and validity of the academic buoyancy construct is important considering that there is currently no instrument specifically used to measure or assess academic buoyancy in Indonesia. The subjects in this study were 1352 junior and senior high school students in Bandung. The academic buoyancy scale used in this study is an adaptation of the academic buoyancy questionnaire developed by Martin and Marsh (2008). The analytical method used is confirmatory factor. The results showed that the items for the academic buoyancy scale had SLF values ??ranging from 0.647 to 0.843 so that all items could be said to be valid. The CR value is 0.823 and the VE is 0.54 which means that the academic buoyancy scale can be trusted. The direction for mass research is to take research subjects from different educational levels so that discussions about academic buoyancy in Indonesia can be more comprehensive. Keywords: Reliability, construct validity, academic buoyancy scale